The Use of Scrabble Game as A Teaching Medium to Improve Students’ Vocabulary Mastery at SMPN 4 Sungguminasa - Nurdin, Ainun Muthmainnah; Sakkir, Geminastiti; Talib, Ahmad (Journal of Excellence in English Language Education, 2024)
This study aims to determine whether using Scrabble games improves students' vocabulary at SMPN 4 Sungguminasa, especially in class VIII. The method used is a pre-experimental research approach by giving a pretest and posttest, with a sample size of 30 students from class VIII.F. The results of the analysis showed that the mean score on the pretest was 31.77, while the mean score on the posttest increased to 79.80. The significance value used in this study is α = 0.05. Based on the results of data processing and statistical tests using the paired sample t-test method, there was a significant difference between the mean scores of the pretest and that of the posttest (p < 0.05). In conclusion, the utilization of Scrabble Game as a teaching medium for the eighth-grade students of SMPN 4 Sungguminasa demonstrated improvement. This was evidenced by the mean score of the posttest (79.80), which was significantly higher than the pretest score (31.77). Furthermore, the results of the t-test indicated that the alternative hypothesis (H1) was accepted, while the null hypothesis (H0) was rejected.